STUDI PERILAKU KONSUMEN DAN IDENTIFIKASI PARAMETER BAKSO SAPI BERDASARKAN PREFERENSI KONSUMEN DI WILAYAH DKI JAKARTA [Study of Consumer Behaviour and Identification of Meat Ball Characteristics Based on Consumer Preferences in DKI Jakarta] - Joko Hermanianto; Ratna Yudtyhia Andayani (Jurnal Teknologi dan Industri Pangan, 2002)
Meat  Ball  is a very popular  meat product in Indonesia, but there is still no quality standard of meat ball based on consumer preferences. The aim of the research was to identify consumer preferences of meat ball. This research was carried ont in three steps, which were consumer survey, sensory evaluation and physical and chemical analysis of meat ball. The results of consumer survey showed that the four factors that affect consumer preferences on meat ball (in priority order) were quality, selling place, price and accessibility. The five quality characteristics of which affect consumer preferences (in priority order) were taste, aroma, texture, color and size. The most favoured meat ball had moderate brothiness, light salt (salt content of 2 %), strong meat flavor with (meat content of + 45%)  boiled meat aroma; moderate tenderness (tenderness values of 0,90 kg/mm – 0,91 kg/mm) and slight chewiness (chewiness value of 0,91 kg/mm); light grey color with L (lightness) value of 53, 77, (a value of 3,77 and b value of 10,36)  round form;  medium size (diameters of 3-5 cm), amount to three to five  meat ball  per serving with reasonable  price of Rp 2.000,- to Rp 3.000,- per serving.